A person-centered assertiveness training intervention in women's groups: A quantitative and qualitative analysis - Αργυρακούλη, Έφη; Ζαφειροπούλου, Μαρία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF